Diatomite-based oil-control composite powder, preparation method thereof and application of diatomite-based oil-control composite powder in oil-control cosmetics

By depositing zinc oxide and β-calcium phosphate on diatomaceous earth, the modified diatomaceous earth-based oil-control composite powder is solved, and the existing oil-control powder absorbs beneficial oils is achieved, and the selective adsorption of unsaturated fatty acids is achieved. and flocculation, extending the durability of the makeup and ensuring safety.

CN119488439APending Publication Date: 2025-02-21CHANGCHUN INSTITUTE OF APPLIED CHEMISTRY CHINESE ACADEMY OF SCIENCES
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411613755.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-13
Publication Date
2025-02-21

AI Technical Summary

Technical Problem

Existing oil-controlled powders also absorb beneficial cosmetic oils when absorbing oil secreted by the skin, and cannot effectively flocculate and solidify the oils, resulting in the long-lasting effect of makeup. At the same time, hydroxyapatite poses a safety risk and cannot be widely used in cosmetics.

Method used

Diatomaceous earth is used as a support, and zinc oxide and β-calcium phosphate are deposited, and graft modification is carried out to form a diatomaceous earth-based oil-controlled composite powder. The composite powder utilizes the porous structure of diatomaceous earth and the interaction of calcium ions with carboxylate to achieve selective adsorption and flocculation of unsaturated fatty acids.

Benefits of technology

It realizes directional adsorption and rapid flocculation of unsaturated fatty acids secreted by the human body, extends the makeup time of makeup, and avoids the absorption of beneficial oils, ensuring the durability and safety of makeup.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119488439A_ABST
    Figure CN119488439A_ABST
Patent Text Reader

Abstract

The invention discloses diatomite-based oil-control composite powder, a preparation method thereof and application of the diatomite-based oil-control composite powder in oil-control cosmetics. The invention belongs to the field of cosmetics. The diatomite-based oil-control composite powder prepared by the invention can be used for replacing hydroxyapatite to act in oil-control cosmetics. The diatomite-based oil control composite powder disclosed by the invention is obtained by modifying and compounding porous minerals. The diatomite-based oil-control composite powder prepared by the experiment is rough in surface and provided with mesopores, unsaturated fatty acid secreted by a human body can be directionally adsorbed and fixed in a porous structure of diatomite by utilizing the porous structure of the diatomite and interaction of calcium ions and carboxylate radicals, and the unsaturated fatty acid is rapidly flocculated and cured, so that the oil-control effect of the diatomite-based oil-control composite powder is improved. The makeup lasting time can be effectively prolonged. The diatomite-based oil-control composite powder prepared by the invention can completely replace hydroxyapatite to play a role in oil-control cosmetics, and is of great significance to development and production of oil-control composite powder cosmetics.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the field of cosmetics, and in particular relates to a diatomaceous earth-based oil-controlling composite powder, a preparation method thereof, and application of the diatomaceous earth-based oil-controlling composite powder in oil-controlling cosmetics. Background Art

[0002] The problem of makeup lasting longer in the summer has become a topic of great concern to many makeup lovers. Targeted oil control technology can absorb excess oil secreted by the skin in a targeted manner, achieving precise targeted oil control. It can absorb oil without affecting the makeup and keep the makeup long-lasting and shiny. In the prior art, porous oil control powders are usually used as oil absorption carriers, such as porous silica, porous polymethyl methacrylate, etc. However, on the one hand, such porous oil control powders do not have selective adsorption. While absorbing the oil secreted by the skin, they also absorb some beneficial oil additives in cosmetics; on the other hand, such oil control powders cannot flocculate and solidify the oil, resulting in the durability of the makeup being affected. In recent years, a hydroxyapatite composite oil-absorbing powder has emerged. Hydroxyapatite uses the calcium ions (Ca) in itself to absorb the oil. 2+ ) can easily bond with the carboxyl group in unsaturated fatty acids (the main oil component of human sweat) to form a stable chemical bond, and selectively absorb unsaturated fatty acids to achieve the effect of directional adsorption of oil. However, hydroxyapatite has safety risks and has been restricted by the European Union for its use in cosmetics. Therefore, finding a safe and harmless substance to replace the role of hydroxyapatite in oil-control cosmetics has broad market prospects in directional oil-absorbing composite powders. Summary of the invention

[0003] The purpose of the present invention is to find a safe and harmless substance to replace the role of hydroxyapatite in oil-control cosmetics. The present invention provides a diatomaceous earth-based oil-control composite powder and a preparation method thereof and an application thereof in oil-control cosmetics.

[0004] The technical solution of the present invention is as follows:

[0005] One of the purposes of the present invention is to provide a method for preparing a diatomaceous earth-based oil-controlling composite powder, the method comprising:

[0006] S1: Disperse diatomaceous earth and diammonium hydrogen phosphate in water, add calcium salt aqueous solution, adjust the pH value to 7, and after the reaction is complete, wash, filter, and dry to obtain β-calcium phosphate / diatomaceous earth composite (β-TCP / diatomaceous earth composite powder);

[0007] S2: Dispersing the diatomite / calcium phosphate complex and sodium carbonate in S1 in water, dropping a zinc salt aqueous solution, and after the reaction is complete, washing, filtering, drying, and calcining to obtain zinc oxide / β-calcium phosphate / diatomite composite powder (ZnO / β-TCP / diatomite composite powder);

[0008] S3: dispersing the zinc oxide / β-calcium phosphate / diatomite composite powder of S2 in toluene, adding a silane coupling agent and an inhibitor, and after the reaction is complete, washing, filtering, and drying to obtain a modified zinc oxide / β-calcium phosphate / diatomite composite powder with a double bond (modified ZnO / β-TCP / diatomite composite powder with a double bond);

[0009] S4: Under nitrogen protection, the modified ZnO / β-TCP / diatomite composite powder with double bonds in S3, the polymerized monomer and toluene are uniformly stirred, an initiator is added, the reaction is continued, washing, filtering, drying and ball milling are performed to obtain a diatomite-based oil-controlling composite powder.

[0010] It is further defined that the silica content of the diatomaceous earth in S1 is greater than 75%, the particle size is 5-50 μm, and the porosity is 20-200 m 2 / g, the calcium salt is calcium nitrate, calcium sulfate or calcium chloride, the mass ratio of diatomaceous earth to diammonium hydrogen phosphate is 5-20:1, and the molar ratio of diammonium hydrogen phosphate to the calcium salt is 1-5:3.

[0011] It is further defined that the zinc salt of S2 is zinc sulfate, zinc nitrate, zinc acetate or zinc chloride, the mass ratio of β-TCP / diatomaceous earth composite powder to zinc salt is 2-10:1, and the molar ratio of sodium carbonate to zinc salt is 1-5:1.

[0012] It is further defined that the calcination of S2 is divided into two stages, the first stage is at a temperature of 400-600°C and a time of 1-3 hours, and the second stage is at a temperature of 700-900°C and a time of 1-3 hours.

[0013] It is further defined that the silane coupling agent of S3 is vinyl trimethoxy silane, vinyl triethoxy silane or γ-methacryloxypropyl trimethoxy silane, and the polymerization inhibitor is catechol.

[0014] It is further defined that the mass ratio of the ZnO / β-TCP / diatomaceous earth composite powder to the silane coupling agent in S3 is 5-20:1, and the mass ratio of the inhibitor to the silane coupling agent is 0.5-5:100.

[0015] It is further defined that the polymerization monomer of S4 is a mixture of divinyl polydimethylsiloxane, terminal amino silicone oil, terminal methyl allyl polyoxyethylene polyoxypropylene ether and terminal vinyl polyoxyethylene ether, the initiator is an azo initiator, the mass ratio of modified ZnO / β-TCP / diatomaceous earth composite powder with double bonds to the polymerization monomer is 10-50:1, and the mass ratio of the initiator to the polymerization monomer is 1:10-50.

[0016] It is further defined that the azo initiator is azobisisobutyronitrile or azobisisoheptylnitrile, and the mass ratio of divinyl polydimethylsiloxane, amino-terminated silicone oil, methyl allyl-terminated polyoxyethylene polyoxypropylene ether and vinyl-terminated polyoxyethylene ether is 1-5:1:1-5:1-5.

[0017] The second object of the present invention is to provide a diatomaceous earth-based oil-controlling composite powder prepared by the above preparation method.

[0018] The third object of the present invention is to provide an application of the diatomaceous earth-based oil-controlling composite powder in oil-controlling cosmetics.

[0019] Compared with the prior art, the specific advantages of the present invention are as follows:

[0020] (1) Tricalcium phosphate (TCP; Ca 3 (PO 4 ) 2 ) is one of the most studied calcium phosphates. It is a calcium phosphate with a Ca / P ratio of 1.5 and is divided into α phase and β phase. The β-TCP selected in this application is similar to the main inorganic components in human bones, has good biocompatibility, is naturally biodegradable, safe and non-toxic. Therefore, β-TCP is an ideal substitute for hydroxyapatite. The diatomite selected in this application is an inorganic non-metallic resource, whose important component is amorphous silicon dioxide. Diatomite has a nano-scale porous structure and a micron-scale size, a large specific surface area, and excellent properties such as strong adsorption.

[0021] (2) The present invention uses diatomaceous earth as a carrier, deposits zinc oxide and β-TCP on the diatomaceous earth, and uses a large number of hydroxyl groups on the surface of zinc oxide to graft-modify the deposited modified diatomaceous earth to form a diatomaceous earth-based oil-control composite powder with a stable structure. The composite powder makes full use of the porous structure of diatomaceous earth and the interaction between calcium ions and carboxyl groups, can directionally adsorb unsaturated fatty acids secreted by the human body and adsorb and fix them in the porous structure of diatomaceous earth, and quickly flocculate and solidify the unsaturated fatty acids, which can effectively prolong the makeup lasting time. BRIEF DESCRIPTION OF THE DRAWINGS

[0022] Figure 1 This is the infrared spectrum of the diatomite-based oil-controlling composite powder prepared in Example 1;

[0023] Figure 2 This is a scanning electron microscope image of the diatomite-based oil-controlling composite powder prepared in Example 1;

[0024] Figure 3 This is a contact angle test diagram of the ZnO / β-TCP / diatomite composite powder prepared in Example 1;

[0025] Figure 4 This is a contact angle test diagram of the diatomaceous earth-based oil-control composite powder prepared in Example 1. DETAILED DESCRIPTION

[0026] In order to make the purpose, technical solution and advantages of the present invention more clearly understood, the present invention is further described in detail below in conjunction with the embodiments. It should be understood that the specific embodiments described herein are only used to explain the present invention and are not used to limit the present invention.

[0027] The experimental methods used in the following examples are conventional methods unless otherwise specified. The materials, reagents, methods and instruments used are conventional materials, reagents, methods and instruments in the art unless otherwise specified, and can be obtained through commercial channels by those skilled in the art.

[0028] The terms "comprising," "including," "having," "containing," or any other variations thereof, as used in the following examples, are intended to cover a non-exclusive inclusion. For example, a composition, step, method, article, or apparatus comprising the listed elements is not necessarily limited to only those elements, but may include other elements not expressly listed or inherent to such composition, step, method, article, or apparatus.

[0029] When equivalent, concentration or other value or parameter is represented by the range limited by range, preferred range or a series of upper preferred value and lower preferred value, this should be understood as specifically disclosing all ranges formed by any pairing of any upper range limit or preferred value and any lower range limit or preferred value, regardless of whether the scope is disclosed separately. For example, when disclosing range "1 to 5", described range should be interpreted as including range "1 to 4", "1 to 3", "1 to 2", "1 to 2 and 4 to 5", "1 to 3 and 5" etc. When numerical range is described in this article, unless otherwise stated, the scope is intended to include its end value and all integers and fractions within the scope. In the present application specification and claims, range limitation can be combined and / or interchanged, if these ranges are not otherwise stated, include all sub-ranges contained therein.

[0030] The indefinite articles "a" and "an" before the elements or components of the present invention have no limitation on the quantity requirements (i.e. the number of occurrences) of the elements or components. Therefore, "a" or "an" should be interpreted as including one or at least one, and the elements or components in the singular form also include the plural form, unless the quantity obviously refers to the singular form only.

[0031] The "one embodiment" or "embodiment" of the present invention refers to a specific feature, structure or characteristic that can be included in at least one implementation of the present invention. The "in one embodiment" that appears in different places in this specification does not refer to the same embodiment, nor is it a separate or selective embodiment that is mutually exclusive with other embodiments.

[0032] The endpoints and any values ​​of the ranges disclosed in the invention are not limited to the precise ranges or values, and these ranges or values ​​should be understood to include values ​​close to these ranges or values. For numerical ranges, the endpoint values ​​of each range, the endpoint values ​​of each range and the individual point values, and the individual point values ​​can be combined with each other to obtain one or more new numerical ranges, which should be regarded as specifically disclosed in this article.

[0033] The following are the materials used in the examples:

[0034] Embodiment 1:

[0035] S1: Weigh 50g of diatomaceous earth with a particle size of 10μm and 10g of diammonium hydrogen phosphate and disperse them in 500ml of water and stir them thoroughly to form a diatomaceous earth and diammonium hydrogen phosphate dispersion, then weigh 15g of calcium nitrate and dissolve it in 50ml of water to form a calcium nitrate aqueous solution, under stirring, add the calcium nitrate aqueous solution to the diatomaceous earth and diammonium hydrogen phosphate dispersion at a rate of 5mL / min, after the dripping is complete, add ammonia water to adjust the pH value to 7, react the system for 6h, filter, and wash with ethanol to obtain a diatomaceous earth loaded powder, place the loaded powder in an oven at 120°C for 10h, and obtain β-TCP calcium phosphate / diatomaceous earth composite powder;

[0036] S2: Weigh 50g of calcium phosphate / diatomite composite powder and 10g of sodium carbonate and disperse them in 500ml of water and stir them thoroughly to form a calcium phosphate / diatomite composite powder dispersion, then weigh 17g of zinc nitrate and dissolve it in 50ml of water to form a zinc nitrate aqueous solution, under stirring, add the zinc nitrate aqueous solution to the calcium phosphate / diatomite composite powder dispersion at a rate of 5mL / min, continue to react for 6h after the addition is completed, then filter and wash, place the obtained solid powder in a 100°C oven for 10h, and then calcine at 500°C for 2h and 800°C for 2h in a muffle furnace to obtain ZnO / β-TCP / diatomite composite powder;

[0037] S3: Weigh 50g ZnO / β-TCP / diatomite composite powder and disperse it in 500ml toluene, then add 5g vinyltriethoxysilane and 0.05g catechol, react at 80°C for 6h, filter, wash with ethanol, filter again, and dry the obtained powder sample in an oven at 60°C for 5h to obtain modified ZnO / β-TCP / diatomite composite powder with double bonds;

[0038] S4: Under nitrogen protection conditions, 50g of modified ZnO / β-TCP / diatomite composite powder with double bonds, 1g of divinyl polydimethylsiloxane, 1g of terminal amino silicone oil, 1g of terminal methyl allyl polyoxyethylene polyoxypropylene ether, 1g of terminal vinyl polyoxyethylene ether and 500g of toluene were added into the reactor, mechanically stirred for 0.5h, and then 0.24g of azobisisobutyronitrile was added, and the reaction was continued for 6h. The reaction solution was then filtered, washed, dried, and then ball milled at 30rpm to obtain a diatomite-based oil-control composite powder.

[0039] Embodiment 2:

[0040] S1: Weigh 50g of diatomaceous earth with a particle size of 20μm and 5g of diammonium hydrogen phosphate and disperse them in 500ml of water and stir them thoroughly to form a diatomaceous earth and diammonium hydrogen phosphate dispersion, then weigh 7.5g of calcium nitrate and dissolve it in 50ml of water to form a calcium nitrate aqueous solution, under stirring, add the calcium nitrate aqueous solution to the diatomaceous earth and diammonium hydrogen phosphate dispersion at a rate of 5mL / min, after the dripping is complete, add ammonia water to adjust the pH value to 7, react the system for 6h, filter, and wash with ethanol to obtain a diatomaceous earth loaded powder, place the loaded powder in an oven at 120°C for 8h, and obtain β-TCP calcium phosphate / diatomaceous earth composite powder;

[0041] S2: Weigh 50g of calcium phosphate / diatomite composite powder and 16g of sodium carbonate and disperse them in 500ml of water and stir them thoroughly to form a calcium phosphate / diatomite composite powder dispersion, then weigh 25g of zinc nitrate and dissolve it in 50ml of water to form a zinc nitrate aqueous solution, under stirring, add the zinc nitrate aqueous solution to the calcium phosphate / diatomite composite powder dispersion at a rate of 5mL / min, continue to react for 6h after the addition is completed, then filter and wash, place the obtained solid powder in a 100°C oven for 12h, and then calcine at 500°C for 2h and 800°C for 2h in a muffle furnace to obtain ZnO / β-TCP / diatomite composite powder;

[0042] S3: Weigh 50g ZnO / β-TCP / diatomite composite powder and disperse it in 500ml toluene, then add 3g γ-methacryloxypropyltrimethoxysilane and 0.05g catechol, react at 80°C for 6h, filter, wash with ethanol, filter again, and dry the obtained powder sample in an oven at 60°C for 5h to obtain modified ZnO / β-TCP / diatomite composite powder with double bonds;

[0043] S4: Under nitrogen protection conditions, 50g of modified ZnO / β-TCP / diatomite composite powder with double bonds, 1g of divinyl polydimethylsiloxane, 1g of terminal amino silicone oil, 1g of terminal methyl allyl polyoxyethylene polyoxypropylene ether, 1g of terminal vinyl polyoxyethylene ether and 500g of toluene were added into the reactor, mechanically stirred for 0.5h, and then 0.24g of azobisisobutyronitrile was added, and the reaction was continued for 6h. The reaction solution was then filtered, washed, dried, and then ball milled at 30rpm to obtain a diatomite-based oil-control composite powder.

[0044] Embodiment 3:

[0045] S1: Weigh 50g of diatomaceous earth with a particle size of 50μm and 2.5g of diammonium hydrogen phosphate and disperse them in 500ml of water and stir them thoroughly to form a diatomaceous earth and diammonium hydrogen phosphate dispersion, then weigh 3.75g of calcium nitrate and dissolve it in 50ml of water to form a calcium nitrate aqueous solution, under stirring, add the calcium nitrate aqueous solution to the diatomaceous earth and diammonium hydrogen phosphate dispersion at a rate of 5mL / min, after the dripping is complete, add ammonia water to adjust the pH value to 7, react the system for 6h, filter, and wash with ethanol to obtain a diatomaceous earth loaded powder, place the loaded powder in an oven at 120°C for 12h, and obtain β-TCP calcium phosphate / diatomaceous earth composite powder;

[0046] S2: Weigh 50g of calcium phosphate / diatomite composite powder and 5g of sodium carbonate and disperse them in 500ml of water and stir them thoroughly to form a calcium phosphate / diatomite composite powder dispersion, then weigh 5g of zinc nitrate and dissolve it in 50ml of water to form a zinc nitrate aqueous solution, under stirring, add the zinc nitrate aqueous solution to the calcium phosphate / diatomite composite powder dispersion at a rate of 5mL / min, continue to react for 6h after the addition is completed, then filter and wash, place the obtained solid powder in a 100°C oven for 12h, and then calcine at 500°C for 2h and 800°C for 2h in a muffle furnace to obtain ZnO / β-TCP / diatomite composite powder;

[0047] S3: Weigh 50g ZnO / β-TCP / diatomite composite powder and disperse it in 500ml toluene, then add 4g vinyltrimethoxysilane and 0.05g catechol, react at 80°C for 6h, filter, wash with ethanol, filter again, and dry the obtained powder sample in an oven at 60°C for 5h to obtain modified ZnO / β-TCP / diatomite composite powder with double bonds;

[0048] S4: Under nitrogen protection conditions, 50g of modified ZnO / β-TCP / diatomite composite powder with double bonds, 1g of divinyl polydimethylsiloxane, 1g of terminal amino silicone oil, 1g of terminal methyl allyl polyoxyethylene polyoxypropylene ether, 1g of terminal vinyl polyoxyethylene ether and 500g of toluene were added into the reactor, mechanically stirred for 0.5h, and then 0.24g of azobisisobutyronitrile was added, and the reaction was continued for 6h. The reaction solution was then filtered, washed, dried, and then ball milled at 30rpm to obtain a diatomite-based oil-control composite powder.

[0049] Embodiment 4:

[0050] S1: Weigh 50g of diatomaceous earth with a particle size of 30μm and 4g of diammonium hydrogen phosphate, disperse them in 500ml of water and stir them thoroughly to form a diatomaceous earth and diammonium hydrogen phosphate dispersion, then weigh 6g of calcium nitrate and dissolve it in 50ml of water to form a calcium nitrate aqueous solution, under stirring, add the calcium nitrate aqueous solution to the diatomaceous earth and diammonium hydrogen phosphate dispersion at a rate of 5mL / min, after the dripping is complete, add ammonia water to adjust the pH value to 7, react the system for 6h, filter, and wash with ethanol to obtain a diatomaceous earth loaded powder, place the loaded powder in an oven at 120°C for 10h, and obtain β-TCP calcium phosphate / diatomaceous earth composite powder;

[0051] S2: Weigh 50g of calcium phosphate / diatomite composite powder and 5g of sodium carbonate and disperse them in 500ml of water and stir them thoroughly to form a calcium phosphate / diatomite composite powder dispersion, then weigh 5g of zinc nitrate and dissolve it in 50ml of water to form a zinc nitrate aqueous solution, and under stirring, drop the zinc nitrate aqueous solution into the calcium phosphate / diatomite composite powder dispersion at a rate of 5mL / min. After the dropwise addition is completed, continue to react for 6h, then filter and wash with water, place the obtained solid powder in an oven at 100°C for 10h, and then calcine at 500°C for 2h and 800°C for 2h in a muffle furnace to obtain ZnO / β-TCP / diatomite composite powder;

[0052] S3: Weigh 50g ZnO / β-TCP / diatomite composite powder and disperse it in 500ml toluene, then add 4g vinyltrimethoxysilane and 0.05g catechol, react at 80°C for 6h, filter, wash with ethanol, filter again, and dry the obtained powder sample in an oven at 60°C for 5h to obtain modified ZnO / β-TCP / diatomite composite powder with double bonds;

[0053] S4: Under nitrogen protection conditions, 50g of modified ZnO / β-TCP / diatomite composite powder with double bonds, 1.5g of divinyl polydimethylsiloxane, 1g of terminal amino silicone oil, 1g of terminal methyl allyl polyoxyethylene polyoxypropylene ether, 1.5g of terminal vinyl polyoxyethylene ether and 500g of toluene were added into the reactor, mechanically stirred for 0.5h, and then 0.24g of azobisisobutyronitrile was added, and the reaction was continued for 6h. The reaction solution was then filtered, washed, dried, and then ball milled at 30rpm to obtain a diatomite-based oil-control composite powder.

[0054] Embodiment 5:

[0055] S1: Weigh 50g of diatomaceous earth with a particle size of 20μm and 8g of diammonium hydrogen phosphate and disperse them in 500ml of water and stir them thoroughly to form a diatomaceous earth and diammonium hydrogen phosphate dispersion, then weigh 7.5g of calcium sulfate and dissolve it in 50ml of water to form a calcium sulfate aqueous solution, under stirring, add the calcium sulfate aqueous solution to the diatomaceous earth and diammonium hydrogen phosphate dispersion at a rate of 5mL / min, after the dropwise addition, add ammonia water to adjust the pH value to 7, react the system for 6h, filter, and wash with ethanol to obtain a diatomaceous earth loaded powder, place the loaded powder in an oven at 120°C for 10h, and obtain β-TCP calcium phosphate / diatomaceous earth composite powder;

[0056] S2: Weigh 50g of calcium phosphate / diatomite composite powder and 16g of sodium carbonate and disperse them in 500ml of water and stir them thoroughly to form a calcium phosphate / diatomite composite powder dispersion, then weigh 20g of zinc sulfate and dissolve it in 50ml of water to form an aqueous zinc nitrate solution, and under stirring, drop the aqueous zinc nitrate solution into the calcium phosphate / diatomite composite powder dispersion at a rate of 5mL / min. After the dropwise addition is completed, continue to react for 6h, then filter and wash with water, place the obtained solid powder in an oven at 100°C for 12h, and then calcine at 500°C for 2h and 800°C for 2h in a muffle furnace to obtain a ZnO / β-TCP / diatomite composite powder;

[0057] S3: Weigh 50g ZnO / β-TCP / diatomite composite powder and disperse it in 500ml toluene, then add 3g γ-methacryloxypropyltrimethoxysilane and 0.05g catechol, react at 80°C for 6h, filter, wash with ethanol, filter again, and dry the obtained powder sample in an oven at 60°C for 5h to obtain modified ZnO / β-TCP / diatomite composite powder with double bonds;

[0058] S4: Under nitrogen protection conditions, 50g of modified ZnO / β-TCP / diatomite composite powder with double bonds, 1g of divinyl polydimethylsiloxane, 1g of terminal amino silicone oil, 1g of terminal methyl allyl polyoxyethylene polyoxypropylene ether, 1g of terminal vinyl polyoxyethylene ether and 500g of toluene were added into the reactor, mechanically stirred for 0.5h, and then 0.24g of azobisisobutyronitrile was added, and the reaction was continued for 6h. The reaction solution was then filtered, washed, dried, and then ball milled at 30rpm to obtain a diatomite-based oil-control composite powder.

[0059] Embodiment 6:

[0060] S1: Weigh 50g of diatomaceous earth with a particle size of 15μm and 4g of diammonium hydrogen phosphate and disperse them in 500ml of water and stir them thoroughly to form a diatomaceous earth and diammonium hydrogen phosphate dispersion, then weigh 6g of calcium chloride and dissolve it in 50ml of water to form a calcium chloride aqueous solution, under stirring, add the calcium chloride aqueous solution to the diatomaceous earth and diammonium hydrogen phosphate dispersion at a rate of 5mL / min, after the dropwise addition, add ammonia water to adjust the pH value to 7, react the system for 6h, filter, and wash with ethanol to obtain a diatomaceous earth loaded powder, place the loaded powder in an oven at 120°C for 8h, and obtain β-TCP calcium phosphate / diatomaceous earth composite powder;

[0061] S2: Weigh 50g of calcium phosphate / diatomite composite powder and 5g of sodium carbonate and disperse them in 500ml of water and stir them thoroughly to form a calcium phosphate / diatomite composite powder dispersion, then weigh 5g of zinc acetate and dissolve it in 50ml of water to form a zinc acetate aqueous solution, under stirring, add the zinc acetate aqueous solution to the calcium phosphate / diatomite composite powder dispersion at a rate of 5mL / min, continue to react for 6h after the addition is completed, then filter and wash, place the obtained solid powder in a 100°C oven for 8h, and then calcine at 500°C for 2h and 800°C for 2h in a muffle furnace to obtain a ZnO / β-TCP / diatomite composite powder;

[0062] S3: Weigh 50g ZnO / β-TCP / diatomite composite powder and disperse it in 500ml toluene, then add 4g vinyltrimethoxysilane and 0.05g catechol, react at 80°C for 6h, filter, wash with ethanol, filter again, and dry the obtained powder sample in an oven at 60°C for 5h to obtain modified ZnO / β-TCP / diatomite composite powder with double bonds;

[0063] S4: Under nitrogen protection conditions, 50g of modified ZnO / β-TCP / diatomite composite powder with double bonds, 1.5g of divinyl polydimethylsiloxane, 1g of terminal amino silicone oil, 1g of terminal methyl allyl polyoxyethylene polyoxypropylene ether, 1.5g of terminal vinyl polyoxyethylene ether and 500g of toluene were added into the reactor, mechanically stirred for 0.5h, and then 0.24g of azobisisobutyronitrile was added, and the reaction was continued for 6h. The reaction solution was then filtered, washed, dried, and then ball milled at 30rpm to obtain a diatomite-based oil-control composite powder.

[0064] Comparative Example 1:

[0065] The difference between Comparative Example 1 and Example 1 is that S1 and S2 are omitted, and 8g ZnO, 15g β-TCP, and 35g diatomaceous earth with a particle size of 10 μm are directly mechanically blended to obtain a mixture that replaces the ZnO / β-TCP / diatomaceous earth composite powder in S3. The other processes are completely the same as those in Example 1.

[0066] Comparative Example 2:

[0067] The difference between Comparative Example 2 and Example 1 is that S1 is omitted, calcium phosphate is not deposited on the surface of diatomaceous earth, 50 g of diatomaceous earth with a particle size of 10 μm is used to replace the calcium phosphate / diatomaceous earth composite powder in S2, and the other processes are completely the same as Example 1.

[0068] Comparative Example 3:

[0069] The difference between Comparative Example 3 and Example 1 is that 10 μm solid silica microspheres are used to replace diatomaceous earth, and the other processes are the same as those in Example 1.

[0070] Figure 1 This is the infrared spectrum of the diatomite-based oil-controlling composite powder prepared in Example 1. As can be seen from the figure, 800cm -1 The Si-O-Si vibration peak appeared at , indicating that the grafting of polysiloxane was successful.

[0071] Figure 2 This is a scanning electron microscope image of the diatomite-based oil-controlling composite powder prepared in Example 1. From the image, it can be seen that the surface of the diatomite-based oil-controlling composite powder is rough and has mesopores, proving that the deposition of zinc oxide and β-TCP on diatomite in this experiment did not block the porous structure of the diatomite itself.

[0072] Figure 3 This is a contact angle test diagram of the ZnO / β-TCP / diatomite composite powder prepared in Example 1. Figure 3 It can be seen that the ZnO / β-TCP / diatomite composite powder prepared in Example 1 has a water contact angle of 0° when it has not undergone chemical modification, and is not hydrophobic.

[0073] Figure 4This is a contact angle test diagram of the diatomite-based oil-controlling composite powder prepared in Example 1. Figure 4 It can be seen that the water contact angle of the diatomite-based oil-control composite powder prepared in Example 1 is 154°, which is hydrophobic, proving that S3 and S4 of this experiment successfully modified the ZnO / β-TCP / diatomite composite powder to obtain a diatomite-based oil-control composite powder with hydrophobicity and selective adsorption.

[0074] Oil absorption test:

[0075] 4 g of the final oil-control powder was weighed from Examples 1-6 and Comparative Examples 1-3, respectively, and mixed evenly with 40 g of oleic acid and 40 g of silicone oil (10 cst), respectively, and allowed to stand at room temperature for 18 h, then 100 ml of petroleum ether was added, magnetically stirred for 30 min, rinsed and filtered, and the residue was calcined at 500 ° C to determine the strong thermal loss. The results are shown in Table 1.

[0076] Flocculation solidification test:

[0077] 2 g of the final oil-control powder was weighed from Examples 1-6 and Comparative Examples 1-3, and 6 g of water and 12 g of oleic acid were added to a glass bottle to prepare simulated artificial sebum. The bottle was shaken up and down rapidly and vigorously for more than 20 times, then allowed to stand, and the glass bottle was gently inverted to observe its fluidity, and the system solidification time was recorded. The results are shown in Table 1.

[0078] Table 1: Experimental table of oil absorption and flocculation solidification results of Examples 1-6 and Comparative Examples 1-3

[0079]

[0080] As shown in Table 1, the diatomite-based oil-control composite powder prepared by the experimental method has high adsorption to oleic acid, and can quickly flocculate and solidify artificial sebum, so as to achieve the effect of effectively controlling oil in cosmetics and maintaining makeup, indicating that the diatomite-based oil-control composite powder prepared by the present invention can completely replace the role of hydroxyapatite in oil-control cosmetics.

[0081] Selective adsorption test:

[0082] Weigh 0.1 g of different types of oils and fats, add 100 mL of n-hexane to dissolve, and mix well. Weigh 0.5 g of the diatomaceous earth-based oil-controlling composite powder prepared in Example 1 into a conical flask, add 50 mL of n-hexane containing oils and fats, seal with a lid, shake for 1 hour, filter, and then analyze by GCMS. The results are shown in Table 2.

[0083] Table 2: Selective adsorption test table of diatomite-based oil-controlling composite powder prepared in Example 1

[0084] Types of Grease Adsorption amount (%) Oleic acid 52.1 White oil 1.2 Silicone oil 2.6 Caprylic Capric Triglyceride 0.8 Squalane 0.3

[0085] From Table 2, we can see that the diatomite-based oil-controlling composite powder prepared by the present invention can selectively absorb oleic acid secreted by the human body, but will not absorb white oil, silicone oil, caprylic capric triglyceride and squalane added in cosmetics, which are oily substances that protect the skin, indicating that this experiment successfully prepared an oil-controlling composite powder with selective adsorption. Combining Tables 1 and 2, it can be seen that the diatomite-based oil-controlling composite powder prepared by the present invention can completely replace the role of hydroxyapatite in oil-controlling cosmetics, and the present invention is of great significance to the development and production of oil-controlling composite powder cosmetics.

[0086] The above are only preferred specific embodiments of the present invention, which are all different implementations based on the overall concept of the present invention, and the protection scope of the present invention is not limited thereto. Any changes or substitutions that can be easily thought of by a person skilled in the art within the technical scope disclosed by the present invention should be included in the protection scope of the present invention. Therefore, the protection scope of the present invention should be based on the protection scope of the claims.

Claims

1. A method for preparing a diatomite-based oil-controlling composite powder, characterized in that: The method: S1: Dispersing diatomaceous earth and diammonium hydrogen phosphate in water, dropping calcium salt aqueous solution, adjusting the pH value to 7, washing, filtering, and drying after the reaction is complete to obtain a β-calcium phosphate / diatomaceous earth composite; S2: Dispersing the diatomaceous earth / calcium phosphate complex and sodium carbonate in water, dropping a zinc salt aqueous solution, and after the reaction is complete, washing, filtering, drying, and calcining to obtain a zinc oxide / β-calcium phosphate / diatomaceous earth complex; S3: dispersing the zinc oxide / β-calcium phosphate / diatomaceous earth composite of S2 in toluene, adding a silane coupling agent and a polymerization inhibitor, and after the reaction is complete, washing, filtering, and drying to obtain a modified zinc oxide / β-calcium phosphate / diatomaceous earth composite with double bonds; S4: Under nitrogen protection, the modified zinc oxide / β-calcium phosphate / diatomaceous earth composite with double bonds in S3, the polymerized monomer and toluene are uniformly stirred, an initiator is added, the reaction is continued, washing, filtering, drying and ball milling are performed to obtain a diatomaceous earth-based oil-controlling composite powder.

2. The method according to claim 1, characterized in that The silica content of S1 diatomaceous earth is greater than 75%, the particle size is 5-50μm, and the porosity is 20-200m 2 / g, the calcium salt is calcium nitrate, calcium sulfate or calcium chloride, the mass ratio of diatomaceous earth to diammonium hydrogen phosphate is 5-20:1, and the molar ratio of diammonium hydrogen phosphate to the calcium salt is 1-5:

3.

3. The method according to claim 1, characterized in that The zinc salt of S2 is zinc sulfate, zinc nitrate, zinc acetate or zinc chloride, the mass ratio of the beta-calcium phosphate / diatomaceous earth composite to the zinc salt is 2-10:1, and the molar ratio of sodium carbonate to the zinc salt is 1-5:

1.

4. The method according to claim 1, characterized in that: The calcination of S2 is divided into two stages, the first stage is at a temperature of 400-600°C and a time of 1-3h, and the second stage is at a temperature of 700-900°C and a time of 1-3h.

5. The method according to claim 1, characterized in that: The silane coupling agent of S3 is vinyl trimethoxysilane, vinyl triethoxysilane or γ-methacryloxypropyl trimethoxysilane, and the polymerization inhibitor is catechol.

6. The method according to claim 1, characterized in that The mass ratio of the zinc oxide / β-calcium phosphate / diatomaceous earth composite to the silane coupling agent in S3 is 5-20:1, and the mass ratio of the polymerization inhibitor to the silane coupling agent is 0.5-5:

100.

7. The method according to claim 1, characterized in that The polymerization monomer of S4 is a mixture of divinyl polydimethylsiloxane, terminal amino silicone oil, terminal methyl allyl polyoxyethylene polyoxypropylene ether and terminal vinyl polyoxyethylene ether, the initiator is an azo initiator, the mass ratio of the modified zinc oxide / β-calcium phosphate / diatomaceous earth complex with double bonds to the polymerization monomer is 10-50:1, and the mass ratio of the initiator to the polymerization monomer is 1:10-50.

8. The method according to claim 7, characterized in that The azo initiator is azobisisobutyronitrile or azobisisoheptanenitrile, and the mass ratio of divinyl polydimethylsiloxane, amino-terminated silicone oil, methyl allyl-terminated polyoxyethylene polyoxypropylene ether and vinyl-terminated polyoxyethylene ether is 1-5:1:1-5:1-5.

9. A diatomaceous earth-based oil-controlling composite powder, characterized in that: Prepared by the method according to any one of claims 1 to 8.

10. Use of the diatomaceous earth-based oil-controlling composite powder according to claim 9 in oil-controlling cosmetics.